IMPLEMENTASI APLIKASI GOOGLE CLASSROOM PADA MATA PELAJARAN IPA TERPADU SELAMA PANDEMI COVID-19 DI KELAS VII-1 SMP NEGERI 2 TEBING TINGGI - Saiyah Saiyah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This purposes of this research is to improve learning result on science subject  through google classroom application. Google classroom can be used to  assist students in developing problem solving skills This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class VII-  Junior High School State 2 Tebing Tinggi which amounted to 37 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the google classroom application of science subjects can improve student learning result characterized by increased mastery learning students, namely the first cycle (70,2%), cycle II (89,1%) and complete learn the clasical equal to 89.1 %. Key word : google-classroom, science